Development of the Massive Open Online Course (MOOC) Module for English for Academic Purposes Course - Rahman Hakim; Rosmania Rima (Journal of English Language Studies, 2024)
This study intends to develop Massive Open Online Course (MOOC) Module for English for Academic Purposes Subject at Sultan Ageng Tirtayasa University. The MOOC aims to equip learners, regardless of department, faculty, or participating campus, with the necessary English language skills to succeed in an academic environment. In order to improve the effectiveness of online learning from these courses, an e-learning platform, such as MOOC, that can accommodate a large number of students from departments and faculties, as well as from other campuses that are members of the Study Program Implementing Collaborative Free Learning Curriculum - Independent Campus". The MOOC is developed through Analysis, Design, Development, Implementation and Evaluation (ADDIE) model that is organized systematically to address issues with learning that relate to instructional media that meet students' requirements and personality traits. A questionnaire was used for evaluation, and the elements were taken directly from the Computer System Usability Questionnaire (CSUQ). The ADDIE (Analysis, Design, construction, Implementation, and Evaluation) approach was used to guide the construction of the MOOC in this study, and the results of the usability evaluation add to the body of knowledge already available on MOOCs. The MOOC achieved a very good rating with an average score of 82.66%, indicating it effectively meets these quality standards. The average score of 78.50% translates to a good rating, indicating a positive user experience with the MOOC. When respondents were asked to comment on the MOOC's strengths the capacity to make students' learning easier emerged as the most prevalent.